Decoupled carbonate chemistry controls on the incorporation of boron into Orbulina universa - Howes, Ella L.; Kaczmarek, Karina; Raitzsch, Markus; Mewes, Antje; Bijma, Nienke; Horn, Ingo; Misra, Sambuddha; Gattuso, Jean-Pierre; Bijma, Jelle (Göttingen : Copernicus GmbH, 2017)
In order to fully constrain paleo-carbonate systems, proxies for two out of seven parameters, plus temperature and salinity, are required. The boron isotopic composition (δ11B) of planktonic foraminifera shells is a powerful tool for reconstructing changes in past surface ocean pH. As B(OH)-4 is substituted into the biogenic calcite lattice in place of CO2- 3 , and both borate and carbonate ions are more abundant at higher pH, it was suggested early on that B = Ca ratios in biogenic calcite may serve as a proxy for [CO2- 3 ]. Although several recent studies have shown that a direct connection of B = Ca to carbonate system parameters may be masked by other environmental factors in the field, there is ample evidence for a mechanistic relationship between B= Ca and carbonate system parameters. Here, we focus on investigating the primary relationship to develop a mechanistic understanding of boron uptake. Differentiating between the effects of pH and [CO2- 3 ] is problematic, as they co-vary closely in natural systems, so the major control on boron incorporation remains unclear. To deconvolve the effects of pH and [CO2- 3 ] and to investigate their impact on the B= Ca ratio and δ11B, we conducted culture experiments with the planktonic foraminifer Orbulina universa in manipulated culture media: Constant pH (8.05), but changing [CO2- 3 ] (238, 286 and 534 μmol kg-1 CO2- 3 ) and at constant [CO2- 3 ] (276±19.5 μmol kg-1) and varying pH (7.7, 7.9 and 8.05). Measurements of the isotopic composition of boron and the B = Ca ratio were performed simultaneously using a femtosecond laser ablation system coupled to a MC-ICP-MS (multiple-collector inductively coupled plasma mass spectrometer). Our results show that, as expected, δ11B is controlled by pH but it is also modulated by [CO2- 3 ]. On the other hand, the B= Ca ratio is driven by [HCO-3 ], independently of pH. This suggests that B= Ca ratios in foraminiferal calcite can possibly be used as a second, independent, proxy for complete paleo-carbonate system ...